Effect on Serum Uric Acid Levels of Drugs Prescribed for Indications other than Treating Hyperuricaemia - Daskalopoulou, S. S.; Tzovaras, V.; Mikhailidis, D. P.; Elisaf, M. (Current Pharmaceutical Design, 2005)
Beyond allopurinol and the well-established uricosuric drugs, several other agents can decrease serum uric acid (SUA) levels, such as losartan, fenofibrate and some non-steroidal anti-inflammatory drugs (NSAIDs). Some of these drugs increase renal urate excretion. Hyperuricaemia and gout are common problems (at least 1% of Western men are affected by gout). Raised SUA levels increase the incidence of acute gout and renal calculi. Hyperuricaemia may also predict an increased risk of vascular events. Therefore, lowering SUA levels is of clinical relevance. In this review we consider the effect on SUA levels of drugs that are prescribed for indications other than treating hyperuricaemia. These drugs may obviate the need for specific treatment (e.g. allopurinol) aimed at lowering SUA levels. Furthermore, because hyperuricaemic patients may already be on several drugs (e.g. due to associated dyslipidaemia, hypertension and/or arthritis) compliance may be improved by avoiding additional medication. The potential for adverse effects associated with polypharmacy would also be decreased.
Keywords: fenofibrate